Pengaruh Pemberian Reward dan Punishment Terhadap Motivasi Kerja Pada Perawat di Ruang Rawat Inap - Erlita Isnaini; Anastasia Lina Dwi Nursanti; Ratna Indriati; Yovita Prabawati Tirta Dharma (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Background: The role of human resources is the main asset of a hospital. Hospitals certainly want to have nurses who perform well and are highly motivated. To increase nurse motivation can be done by giving rewards and punishments. With high work motivation, it will affect the performance of nurses. Research Objective: Knowing the effect of reward and punishment on work motivation both partially and simultaneously. Research Design: This research is a quantitative research with Kendall's Tau test analysis and Logistic Regression test. Research Subjects: The subjects in this study were nurses totaling 133 people. The sampling technique used purposive sampling. Research Results: Reward affects nurses' work motivation (p-value = 0.005). Punishment affects nurses' work motivation (p-value = 0.000). Reward and punishment together affect nurses' work motivation (p-value = 0.000). Conclusion: the conclusion of this study is that reward and punishment have a significant effect on work motivation.